Broadband Spin‐Driven Anomalous Surface Plasmon Polariton Steering via V‐Shaped Aperture Metasurfaces. Issue 2 (20th December 2018) - Yang, Hui; Cao, Guangtao; Ou, Kai; Li, Guanhai; Chen, Xiaoshuang
Abstract: Numerically and theoretically the realization of broadband spin‐driven anomalous surface plasmon polaritons (SPP) steering via a V‐shaped aperture metasurface is demonstrated. With various orientation angles, asymmetrical phase profiles can be achieved on the left and right sides of the V‐shaped aperture, which also exhibit spin sensitive character. Spin‐driven anomalous SPP steering such as SPP launching and focusing are numerically demonstrated by properly arranging the V‐shaped apertures, and enabling extra degrees of freedom in controlling the propagation of SPPs. It is worth noting that spin‐driven anomalous SPP launching can be achieved within a broad bandwidth (800–1100 nm), being more conducive to practical applications. Moreover, an improved theoretical model is established as a physical interpretation of anomalous SPP wavefront steering and the theoretical results agree well with numerical results. These results will largely enhance the flexibility and tunability to steer the wavefront of SPPs, giving rise to broad applications in plasmonic circuits, polarization sensitive beam splitting, and near‐field imaging. Abstract : Spin‐driven anomalous surface plasmon polariton (SPPs) steering such as SPP launching and focusing is numerically demonstrated in a gold metasurface . To further investigate the physical mechanism, an improved theoretical model is established, with which the simulation results are well reproduced. These results will largely enhance the tunability of SPPs, giving rise to broad applications in plasmonic circuits.